2006
DOI: 10.1007/s00122-006-0257-7
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning of nine S alleles and establishment of a PCR-RFLP system for genotyping European pear cultivars

Abstract: Nine full-length cDNAs of S ribonucleases (S-RNases) were cloned from stylar RNA of European pear cultivars by RT-PCR and 3' and 5' RACE. Comparison of the nucleotide sequences between the nine S-RNases cloned and 13 putative S alleles previously amplified by genomic PCRs revealed that seven corresponded to Sa, Sb, Sd, Se, Sh, Sk and Sl alleles, and the other two were new S alleles (designated as Sq and Sr alleles). Genomic PCR with a set of a8FTQQYQa9 and a8EP-anti-IIWPNVa9 primers was used to amplify nine S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 24 publications
3
34
0
Order By: Relevance
“…Since the first report characterizing S-RNase sequences in this species (Zuccherelli et al 2002), 19 alleles have been published (Zuccherelli et al 2002;Zisovich et al 2004;Takasaki et al 2006;Moriya et al 2007;Sanzol and Robbins 2008). Takasaki et al (2006) and Moriya et al (2007) provided full-length cDNA and genomic sequences for 17 S-RNases, confirming that they have all the structural features found in the Maloideae S-RNase. This gene has three main characteristics that make it suitable for molecular S-genotyping: First, five conserved consensus regions (C1-C3, RC4, and C5) and the conserved sequence encoding "IIWPNV" located just downstream of the hyper-variable region (HVR), can be used to simultaneously amplify a large number of alleles using consensus PCR.…”
Section: Introductionmentioning
confidence: 51%
See 2 more Smart Citations
“…Since the first report characterizing S-RNase sequences in this species (Zuccherelli et al 2002), 19 alleles have been published (Zuccherelli et al 2002;Zisovich et al 2004;Takasaki et al 2006;Moriya et al 2007;Sanzol and Robbins 2008). Takasaki et al (2006) and Moriya et al (2007) provided full-length cDNA and genomic sequences for 17 S-RNases, confirming that they have all the structural features found in the Maloideae S-RNase. This gene has three main characteristics that make it suitable for molecular S-genotyping: First, five conserved consensus regions (C1-C3, RC4, and C5) and the conserved sequence encoding "IIWPNV" located just downstream of the hyper-variable region (HVR), can be used to simultaneously amplify a large number of alleles using consensus PCR.…”
Section: Introductionmentioning
confidence: 51%
“…2a). Moreover, the restriction site utilized for the recognition of S r (Takasaki et al 2006) does not exist in S 9 (Fig. 2a).…”
Section: Genomic Characterization Of S-rnases In European Pear Cultivarsmentioning
confidence: 96%
See 1 more Smart Citation
“…The other products, which were different in size from the S 1 -to S 9 -RNases in Japanese pear, were cloned into pCR 2.1 vector and sequenced. Homology searching by BLASTN showed that PCR products of 998 bp from 'Senryo', 536 bp from 'Kuroki', and 309 bp from 'Hogyoku' were 100% homologous at the DNA level to the S e -RNase in European pear (Takasaki et al, 2006), the S 12 -RNase in Chinese pear (accession no. EU117115), and S 30 -RNase in Chinese pear (accession no.…”
Section: Resultsmentioning
confidence: 99%
“…In European pear, 17 S-alleles are found from 95 cultivars (Moriya et al, 2007;Takasaki et al, 2006). In Chinese pear, 32 S-RNase alleles have been cloned from 38 cultivars, and deposited in the DDBJ/EMBL/GenBank database (Tan et al, unpublished; Zhang et al, unpublished).…”
Section: Introductionmentioning
confidence: 99%